2008
DOI: 10.1002/ijc.23873
|View full text |Cite
|
Sign up to set email alerts
|

Biological aggressiveness of prostate cancer in the Finnish screening trial

Abstract: Prostate cancer aggressiveness was evaluated based on pathologic characterization of cases detected in the Finnish prostate cancer screening trial. The trial population consists of 80,458 men aged 55-67 years. A total of 32,000 men were randomized to the screening arm. The remaining 48,000 men formed the control arm. The interval cases and cancers among nonparticipants and in the control arm were identified from the Finnish Cancer Registry. Random samples were selected from screen-detected cases (126 of 543 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, to our knowledge, there are no studies conducted on a large conservatively treated cohort with outcome data, where decisions on future treatment could be indicated, and a very recent paper (Laurila et al, 2009) suggested that further studies are needed to show the final outcome of proliferative activity in patients with watchful waiting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, there are no studies conducted on a large conservatively treated cohort with outcome data, where decisions on future treatment could be indicated, and a very recent paper (Laurila et al, 2009) suggested that further studies are needed to show the final outcome of proliferative activity in patients with watchful waiting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been investigated on TURP material (Feneley et al, 1996), biopsy material (Szende et al, 1999;Cowen et al, 2002;Ojea et al, 2004) and radical prostatectomy series (Bettencourt et al, 1996;Moul, 1999;Zudaire Bergera et al, 2000;Inoue et al, 2005) in large screening programmes (Laurila et al, 2009) and after radiation therapy . Some of these show that Ki-67 is an independent predictor of outcome on multivariate analysis .…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study [69] demonstrated that cancer diagnosed at an initial screening (prevalent cancer) versus cancer diagnosed at later screenings (incident cancer) was associated with shorter time to PSA failure after radical prostatectomy. Similarly, prevalent compared with incident cancers have been associated with higher PSA, larger tumor volume, more advanced clinical stage, and higher Gleason scores [58,67,72]. …”
Section: Prostate-specific Antigen In Prostate Cancer Screeningmentioning
confidence: 99%
“…Because cancers detected by screening are smaller and often better differentiated than clinically detected tumors [1], a definitive diagnosis of prostate adenocarcinoma has become more challenging for the pathologist [2]. Approximately 1% to 2% of small cancers are overlooked when using hematoxylin-eosin (H&E) staining [3,4].…”
Section: Introductionmentioning
confidence: 99%